DO FIRM SIZE AND FIRM AGE MATTER FOR SDG DISCLOSURE? EVIDENCE FROM INDONESIA - Fitri Nuryanti; Wika Harisa Putri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study examines the effect of firm size and firm age on the number of Sustainable Development Goals (SDG) disclosures among publicly listed companies on the Indonesia Stock Exchange during 2023–2024. Using a quantitative approach and purposive sampling, this study analyzes 404 firm-year observations from companies that published annual or sustainability reports and disclosed SDG-related information. SDG disclosure is measured through content analysis using a binary scoring approach across the 17 SDGs. The data are analyzed using Poisson regression, with Ordinary Least Squares (OLS) regression and robust standard errors as a robustness check. The results show that firm size has a positive and significant effect on the number of SDG disclosures, indicating that larger firms tend to disclose SDG-related information more extensively. In contrast, firm age has no significant effect, suggesting that a longer operating history does not necessarily lead to broader SDG disclosure. This study provides empirical evidence that resource capacity and public visibility are more relevant than organizational age in explaining SDG disclosure among Indonesian listed companies. Keywords: firm age, firm size, SDG disclosure, sustainability report, publicly listed companies